Who Thinks about the Competition? Managerial Ability and Strategic Entry in US Local Telephone Markets - Goldfarb, Avi; Xiao, Mo (American Economic Review, 2011)
We examine US local telephone markets shortly after the Telecommunications Act of 1996. The data suggest that more experienced, better-educated managers tend to enter markets with fewer competitors. This motivates a structural econometric model based on behavioral game theory that allows heterogeneity in managers' ability to conjecture competitor behavior. We find that manager characteristics are key determinants in managerial ability. This estimate of ability predicts out-of-sample success. Also, the measured level of ability rises following a shakeout, suggesting that our behavioral assumptions may be most relevant early in the industry's life cycle. (JEL L96, L98, M10)